Regulatory framework for fish cage operation in Calape Bay, Bohol a recommendation based on environmental and culture conditions. - Corrales, Joezen Dizon (University of the Philippines in the Visayas-Cebu College, 2005)
Mariculture has been widely promoted in the Philippines primarily to augment fish production and provide supplemental livelihood to small scale fishers. Due to the expected economic benefits derived from mariculture, its expansion has taken place at a faster pace than expected. However, regulatory guidelines are seldom in place to make this activity sustainable. This study assesses the regulatory mechanisms for fish cage operation in Calape Bay, Bohol. Environmental and culture conditions in the area were used was to come up with a management and regulatory framework that will help local and national governments in ensuring sustainable mariculture operation. Coral reef communities and fish population were surveyed near and away the vicinity of culture areas. Also, water and sediment quality within and outside the fish culture zones were compared. Results of the one-way ANOVA revealed that no significant difference exists as to the hard coral cover near and away the vicinity of fish culture areas. Fish density was highest in the area close to the fish cages but dominated by Apogon spp. Water quality parameters were within the DENR criteria for class SA -water for propagation purposes. The rate of sedimentation in cage areas was relatively higher than in areas without cages. an interview was conducted using a prepared survey questionnaire to determine demographic profile of the fisherfolks, fishing practices and perception on the presence of fish cages in the area. Fishfarms operators were interviewed to assess culture operations. The respondents have negative perceptions on the status of Calape Bay (e.g. marine habitats and resource utilization) as well as the impacts of fish cage operation on their livelihood and the bay's ecosystem.. Results of the Pearson Product Moment Correlation tests showed that the respondents' level of perception on the status of Calape Bay was significantly correlated with age (p<.05) and very significantly correlated with years in fishing (p<.01). Their perception towards the status of amrine habitats is likewise very significsntly correlated with household size (p<.01). The only regulatory mechanism implemented by the local government unit for fish cage operation in Calape Bay was the collection of business tax fr revenue generation.